Emerging Zoonoses: Eco-Epidemiology, Involved Mechanisms and Public Health Implications - A. Paulo Gouveia Almeida; Juan Carlos Navarro; Ruben Bueno-Mari (Frontiers Media SA, 2015)
Zoonoses are currently considered as one of the most important threats for public health worldwide. Zoonoses can be defined as any disease or infection that is naturally transmissible from vertebrate or invertebrate animals to humans and vice-versa. Approximately 75% of recently emerging infectious diseases affecting humans are diseases of animal origin; approximately 60% of all human pathogens are zoonotic. All types of potential pathogenic agents, including viruses, parasites, bacteria and fungi, can cause these zoonotic infections. From the wide range of potential vectors of zoonoses, insects are probably those of major significance due to their abundance, high plasticity and adaptability to different kinds of pathogens, high degrees of synanthropism in several groups and difficulties to apply effective programs of population control. Although ticks, flies, cockroaches, bugs and fleas are excellent insects capable to transmit viruses, parasites and bacteria, undoubtedly mosquitoes are the most important disease vectors. Mosquito borne diseases like malaria, dengue, equine encephalitis, West Nile, Mayaro or Chikungunya are zoonoses with increasing incidence in last years in tropical and temperate countries. Vertebrates can also transmit serious zoonoses, highlighting the role of some carnivorous animals in rabies dissemination or the spread of rodent borne diseases in several rural and urban areas. Moreover, the significance of other food borne zoonoses such as taeniasis, trichinellosis or toxoplasmosis may not been underestimated. According to WHO, FAO and OIE guidelines an emerging zoonotic disease can be defined as a zoonosis that is newly recognized or newly evolved, or that has occurred previously but shows an increase of incidence or expansion in geographical, host or vector range. There are many factors that can provoke or accelerate the emergence of zoonoses, such as environmental changes, habitat modifications, variations of human and animal demography, pathogens and vectors anomalous mobilization related with human practices and globalization, deterioration of the strategies of vector control or changes in pathogen genetics. To reduce public health risks from zoonoses is absolutely necessary to acquire an integrative perspective that includes the study of the complexity of interactions among humans, animals and environment in order to be able to fight against these issues of primary interest for human health. In any case, although zoonoses represent significant public health threats, many of them still remain as neglected diseases and consequently are not prioritized by some health international organisms.
English
Keywords: trypanosomatids; epidemiology; Borrelia; one health; emerging infectious diseases; vector borne diseases; Brucella; zoonoses; rickettsiae; arbovirus